Pathogenesis, epidemiology and control of Group A Streptococcus infection - Brouwer, Stephan; Rivera-Hernandez, Tania; Curren, Bodie F; Harbison-Price, Nichaela; De Oliveira, David M P; Jespersen, Magnus G; Davies, Mark R; Walker, Mark J (Nature reviews. Microbiology, 2023)
Streptococcus pyogenes (Group A Streptococcus; GAS) is exquisitely adapted to the human host, resulting in asymptomatic infection, pharyngitis, pyoderma, scarlet fever or invasive diseases, with potential for triggering post-infection immune sequelae. GAS deploys a range of virulence determinants to allow colonization, dissemination within the host and transmission, disrupting both innate and adaptive immune responses to infection. Fluctuating global GAS epidemiology is characterized by the emergence of new GAS clones, often associated with the acquisition of new virulence or antimicrobial determinants that are better adapted to the infection niche or averting host immunity. The recent identification of clinical GAS isolates with reduced penicillin sensitivity and increasing macrolide resistance threatens both frontline and penicillin-adjunctive antibiotic treatment. The World Health Organization (WHO) has developed a GAS research and technology road map and has outlined preferred vaccine characteristics, stimulating renewed interest in the development of safe and effective GAS vaccines.